Keanekaragaman Tanaman Obat di Masyarakat Lokal Semerap, Kabupaten Kerinci, Jambi (Jurnal Hutan dan Masyarakat, 2023)
Indonesia has a great potential for recognition due to its diversity of plants. Local populations employ these herbs as traditional medicine thanks to their wisdom and understanding. Most of this information is passed on from one generation to the next by parents to their offspring. Semerap Village, Kerinci Regency, Jambi is a small communities in Indonesia that continue to employ plants as therapeutic components. The study was carried out in March 2022. Purposive sampling was employed to collect data, and information on plant species was gathered in the form of regional names, scientific names, family names, Indonesian names, components used, usage patterns, and growth environments. Following the creation of tables and graphs, a descriptive analysis of the data was conducted. The findings revealed that the Semerap people used 25 different varieties of medicinal plants, with leaves serving as the most common plant organ. These kinds of plants are acquired or cultivated in the yard and are typically utilized for drinking. The majority of medicinal plant habitats are located in yards. In general, medicinal plants are consumed or used topically to the body. Keywords: Semerap Local Community, Medicinal Plants, Kerinci